The cytological pattern of cervical papanicolaou smear in a tertiary hospital of India - Ajay Gupta; Pushpendra Singh; Krishna Dubey; Sushil Mewara; Mayank Sharma; Yogesh Gupta (Asian Journal of Medical Sciences, 2023)
Background: Cervical cancer continues to be listed among the top gynecologic cancers worldwide. According to current data, it is ranked fourteenth among all cancers and fourth-ranked cancer among women worldwide. In India alone 1,30,000 new cases occur with the death toll of 70,000 per year. A “PAP’ test should be performed during the second half of the menstrual cycle (Day 14). The patient is placed in lithotomy position and the cervix is visualized by means of a speculum. The smaller end of the Ayre’s spatula is introduced through the external os and the squamocolumnar junction is scraped by rotating the spatula to 360°. Aims and Objectives: The objective of the study is to evaluate the use of the Pap smear screening method for detection of precancerous lesions. Cervical cancer accounts for 15% of all cancers in females. If treated or detected earlier, cervical cancer can be prevented. Materials and Methods: This study was done on 1000 patients during reproductive and later age groups (postmenopausal), attending Obstetric and Gynaecological Outpatient Department of Panna Dhai Hospital associated with RNTMC, Udaipur during the period of November 2012–April 2014 with history of white discharge per vagina, bleeding per vagina, pain in lower abdomen and post coital bleeding. Results: Most of the smears (90.1%) were NILM and 9.9% of smears showed cytological abnormality. Majority 834 (83.4%) of smears were inflammatory, Bacterial vaginosis was seen in 119 cases (11.9%), Candidiasis in 78 cases (7.8%), Trichomoniasis in 35 cases (3.5%), Atrophic vaginitis in 4 cases (0.4%) and Radiation changes in 4 cases (0.4%). There were 99 samples reported as having epithelial cell abnormality. Out of which 75 were LSIL, 14 were high grade squamous intraepithelial, 5 were atypical squamous cells (ASC)-US, 1 was ASC-H and 4 were squamous cell carcinoma. Conclusion: Due to high sensitivity, specificity and accuracy found in this study Pap test is proved to be highly useful to detect precancerous and cancerous lesions of cervix. From the above facts, it can be concluded that early diagnosis and prompt specific treatment of preinvasive or early stages of the disease (mainly in high risk women), reduces the prevalence of invasive carcinoma of uterine cervix.